Penggunaan Ekstrak Etanol Daun Salam (Syzygium polyanthum Wight) pada Sosis Daging Sapi untuk Penghambatan Kerusakan Oksidatif - Priscacylia Clarita Rasini Pirimoy; Rohadi Rohadi; Iswoyo Iswoyo (Agricultural Faculty, 2019)
Oxidation is a major cause of damage to fats and fatty prcts. Beef sausages are susceptible to quality damage due to oxidation. The synthetic antioxidants BHA and BHT are often added to sausages for inhibition of fat oxidation. Consumers have not fully received the use of synthetic antioxidants, because they worry about the negative impact in health. This study aimed to analyze the effect of adding salam leaves (EEDS) ethanolic extract at various concentrations (500, 750, 1000, 1250 and 1500 ppm) on the inhibition of oxidative damage to beef sausage during storage (0-114 hours) at room temperature. This study used randomized complete design (RAL) of one factor (EEDS concentration) with 6 treatments, 3 replications. Variables include peroxide number, acid and thiobarbituric acid reactive substances (TBARS) number. Data analysis used in this study was variance analysis (ANOVA), if there were significant differences between treatments, it was carried out further testing by using Duncan's Multiple Range Test (DMRT) at the 5% level. Data were presented as mean ± standard deviation (SD). The result showed that the values of total phenolic and EEDS flavonoids were 13.36 ± 0.49 g-GAE / 100g and 1.67 ± 0.018 g-QE / 100g, respectively. The antioxidant activity of EEDS in the radical scavenging activity (RSA) -DPPH test was stronger than the BHT, it was respectively 75.68% and 60% (60 μl / ml). There was a significant difference in the value of peroxide number, acid number and TBARS of beef sausage in addition to various EEDS concentrations (500-1500 ppm) during storage (p 0.05). The addition of EEDS 1500 ppm was the most effective against the inhibition of oxidative damage in beef sausage.